Pengaruh Motivasi Belajar Terhadap Hasil Belajar Siswa Di SMA Kota Ambon - Lambertus J. Lokollo; Emma Rumahlewang; Rosmalyn Tutupary (Peneliti.net, 2019)
This study aims to determine the effect of learning motivation and study habits on the learning outcomes of high school students in Ambon City. Survey research was conducted at SMA Ambon samples included 200 students drawn at random(randomsampling).Testing the research hypothesis using multiple regression analysis with SPSS. The results of this study conclude that: (1) there is a significant effect of learning motivation on student learning outcomes, (2) there is a significant effect of learning habits on student learning outcomes, and (3) there is a joint effect of learning motivation and learning habits on learning outcomes students. Based on the results of this study, it was recommended that improving student learning outcomes required increased learning motivation and study habits.